Research on the application effect of self-transcendence nursing model in patients with gestational diabetes mellitus: a randomised controlled trial - Mengpei Xu; Ying Wu; Yaqing Zhou; Zhongmei Lv; Wei Chen; Jingjing Fan (BMC Pregnancy and Childbirth)
Abstract Background Gestational diabetes mellitus is hyperglycemia in special populations (pregnant women), however gestational diabetes mellitus (GDM) not only affects maternal health, but also has profound effects on offspring health. The prevalence of gestational diabetes in my country is gradually increasing. Objective To study the application effect of self-transcendence nursing model in GDM patients. Methods One hundred fourteen GDM patients undergoing prenatal examination in Hai'an People’s Hospital from January 2019 to November 2021 were selected and divided into two groups of 57 cases respectively according to the principle of random single blind. The patients in the control group should receive pregnancy health care under the routine nursing mode, while those in the observation group should receive pregnancy health care under the self-transcendence nursing mode. Then, we would compare the insulin utilization rate, admission before delivery, gestational weeks, delivery outcome and neonatal conditions between the two groups, examine the changes of blood glucose related indexes in the two groups and evaluate the differences between the two groups' Diabetes Distress Scale (DDS) scores and Chinese Versions of Diabetes Management Self-efficacy Scale (C-DMSES) scores. Results The number of hospital admissions (1.12 ± 0.31) and the hospital stay (7.54 ± 1.45) days in the observation group were less than those in the control group (1.56 ± 0.42) and (10.23 ± 2.32) days. There was no difference between the two groups after statistical analysis of gestational weeks and insulin utilization rate (P > 0.05). After the intervention, the total DDS score and emotional burden, doctor/life law/interpersonal relationship related distress score of GDM in the two groups were lower than those before the intervention, while the scores of healthy diet, regular exercise, regular monitoring of blood glucose and medication compliance in C-DMSES were higher than those before the intervention. In addition, the improvements of overall DDS scores and C-DMSES scores of GDM in the observation group were significantly better than those in the control group, so there was statistical significance (P < 0.05). In terms of the pregnancy outcomes and neonatal conditions, the rates of premature delivery and neonatal delivery in the observation group were higher than those in the control group, and there was no difference (P > 0.05) in other aspects of pregnancy outcomes and neonatal conditions. Conclusion Self-transcendence nursing mode intervention can improve blood sugar, reduce psychological distress, and improve self-efficacy in GDM patients, thereby reducing the rate of pregnancy-induced hypertension and premature birth.